Clinical and Physiological Characterization of Elevated Plasma Glucagon-Like Peptide-1 Levels (Hyperglipemia) in a Dipeptidyl Peptidase IV Mutation Carrier - Zhao, Dandan; Zhao, Shaoqian; Wang, Xiao; Su, Mingbo; Liu, Wen; Ma, Qinyun; Hong, Jie; Gu, Weiqiong; Li, Jingya; Liu, Ruixin; Ning, Guang; Wang, Jiqiu; et al. (Frontiers in Endocrinology, 2018)
The clinical application of dipeptidyl peptidase IV inhibitors (DPP4i) increasing active glucagon-like peptide-1 (AGLP-1) levels has been linked to pancreatitis, pancreatic tumors and cardiovascular events. However, DPP4 mutations in humans or the long-term outcomes of high GLP-1 exposure have not been reported. A trio family with a proband showing an extremely high AGLP-1 level (defined here as hyperglipemia [hyper-Glucagon-Like Peptide-1-emia]) was conducted whole-exome sequencing for potential pathogenic genetic defects. One novel DPP4 mutation, p.V486M (c.1456 G>A), was identified in the proband and showed damaged enzymatic activity of DPP4. And ex vivo functional study further showed that the serum from the proband enhanced insulin production of primary rat islet cells. Furthermore, for the V486M variant and other eight DPP4 variants identified in our in-home database, seven of them showed decreased enzymatic activities than wild-type DPP4. Of note, the levels of glucose, lipids and tumor markers (especially for CA15-3 and CA125), increased gradually in the proband during a 4-year follow-up period, although no abnormal physical symptoms or imaging results were observed till now. The other two old carriers in the pedigree both had type 2 diabetes, and one of them had hyperlipidemia and myocarditis additionally. In summary, we firstly identified hyperglipemia in a female subject harboring a loss-of-function DPP4 mutation with decreased DPP4 activity. Other sporadic DPP4 mutations verified the low-frequency occurrence of genetic inhibition of DPP4 activity, at least in the Chinese population. These results may provide new evidence for evaluation of the potential long-term effects of DPP4i and GLP-1 analogues.